2017
DOI: 10.18632/oncotarget.22273
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of the pretreatment serum gamma-glutamyltransferase levels in Chinese patients with non-metastatic cervical cancer

Abstract: This study was performed to evaluate the prognostic significance of the pretreatment serum gamma-glutamyltransferase (GGT) levels in a Chinese cohort of patients with early-stage or locally advanced cervical cancer. The pretreatment serum GGT levels were examined in 290 cervical cancer patients with stage I-III disease and 230 healthy controls selected from a cancer-free population in the same region. Patients were assigned to normal or high-risk GGT groups, as previously described, and the GGT levels were cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Recently, two meta-analyses demonstrated that patients with a high serum GGT level not only had a poor prognosis (in terms of overall survival, recurrence-free survival, and disease-free survival) but also had several unfavorable clinicopathological features, including vascular invasion and the tumor burden [ 5 , 6 ]. Similar findings were also reported in other organs, including the uterus [ 81 , 82 , 83 , 84 , 85 ], colorectum [ 86 ], ovaries [ 23 ], esophagus [ 87 , 88 ], breasts [ 89 , 90 ], gallbladder [ 91 ], nasopharynx [ 92 , 93 ], stomach [ 74 , 94 ], lungs [ 95 ], and pancreas [ 96 ]. In urogenital organs, too, recent studies have demonstrated that serum GGT can predict survival in patients with advanced GU cancer, including RCC [ 11 , 12 ], PC [ 13 ], and UC [ 14 ].…”
Section: Elevation Of Serum Ggt In Patients With Gu Cancersupporting
confidence: 77%
“…Recently, two meta-analyses demonstrated that patients with a high serum GGT level not only had a poor prognosis (in terms of overall survival, recurrence-free survival, and disease-free survival) but also had several unfavorable clinicopathological features, including vascular invasion and the tumor burden [ 5 , 6 ]. Similar findings were also reported in other organs, including the uterus [ 81 , 82 , 83 , 84 , 85 ], colorectum [ 86 ], ovaries [ 23 ], esophagus [ 87 , 88 ], breasts [ 89 , 90 ], gallbladder [ 91 ], nasopharynx [ 92 , 93 ], stomach [ 74 , 94 ], lungs [ 95 ], and pancreas [ 96 ]. In urogenital organs, too, recent studies have demonstrated that serum GGT can predict survival in patients with advanced GU cancer, including RCC [ 11 , 12 ], PC [ 13 ], and UC [ 14 ].…”
Section: Elevation Of Serum Ggt In Patients With Gu Cancersupporting
confidence: 77%
“…Until now, there has been no consensus on the optimal cutoff value for serum GGT levels. In the current study, we selected the final quintile (29 U/L) of all patients' pre-therapeutic serum GGT levels for stratification, which is also a median value between the average (24 U/L) and the cutoff value of previous GGT cancer risk groups (36 U/L) [ 8 12 13 16 17 ]. The final quintile is often used as the stratified value of a risk model in other clinical studies [ 18 19 ]; hence, we considered it reasonable to use it in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have also indicated that GGT is a prognostic biomarker for several cancers in the adjuvant or rescue settings, such as in cervical cancer [ 13 ], endometrial cancer [ 12 ], renal cell carcinoma [ 14 ], and primary metastatic breast cancer [ 8 ]; nevertheless, data for patients receiving NAC are limited. Previous reports have focused on the relationship between serum GGT levels and survival and have not assessed treatment responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, serum GGT combined with other serum biomarkers were effective diagnostic markers of AFP-negative HCC, especially in individuals with early stage, small size or good liver function (42). More researchers continue to assess the prognostic role of serum GGT in cervical cancer (43), esophageal squamous cell carcinoma (44), ovarian cancer (45), renal cell carcinoma (25), and HCC (46). By carrying out a clinical analysis, Zhang et al (15) found that a high concentration of serum GGT was positively associated with advanced TNM stage and large tumor size and was an independent element for predicting the OS rate of patients with primary HCC.…”
Section: A B D Cmentioning
confidence: 99%